Effect of Oxidation of Some Aluminum Alloys on X-ray Attenuation Coefficients - Farid M. Mohammed; Raed N. Razooqi; Sokayna E. Yusuf (Journal of Madenat Alelem University College, 2012)
Characteristic X-ray of 35KV (Mo-Tube) was used to determine the attenuation coefficients of x-ray for some of aluminum alloys with different thicknesses after oxidized them at different times and temperatures. By graphic figures and the phases formation on each sample's surfaces, we studied the effect of oxidation circumstance on absorption. The phases (θ- Al2O3) and (GeO2 ) were formatted on alloy A, (θ- Al2O3), (GeO2 ) and (AlGe0.0435) on alloy B, (MgO) and (Al2SiO5) on alloy C hence we found direct proportion between absorption logarithm with thickness and equivalent thickness for alloy C , while we got inverse proportions for alloys A and B which was due to the phases formation on their surfaces, we found absorption logarithm for alloy C increased with ratio 0.178% after 4 hours later comparing with the same sample at same circumstances after the first half hour. The relation between the half value thickness and mean free path with attenuation coefficients were determined also.